KEPATUHAN WAJIB PAJAK KOPERASI - RADEN ALEM JANITRA (Jurnal Bisnis dan Akuntansi, 2019)
Tax has a big role as a source of state revenue. Tax has a big role as a source of state revenue. Because taxes have an important role,then the tax sector revenue to be something that is reliable, when the natural resource sector revenue unreliable. Indonesia is one country that has problems related to the lack of awareness of taxpayers to pay taxes. The impact of a lack of public awareness in fulfilling obligations is not achieving the percentage of tax revenue in accordance with previously determined. This study aims to examine the effect of the application of the modernization of the tax administration system, knowledge of taxation and tax sanctions on taxpayer compliance.